Reaksi Pasar atas Pergantian Nama Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2012–2022 - Gunawan, Dewa Ngakan Putu Hary; Wirama, Dewa Gede (Fakultas Ekonomi Universitas Samudra, 2024)
The aim of research is to analyze market reactions to changes in names of companies listed on the Indonesia Stock Exchange in 2012-2022. The information content of a company name change is tested based on market reactions as proxied by cumulative abnormal returns. The event study approach is used with a window period of seven days with the event date being the date the company decides to change its name at the RUPS/RUPSLB. Sampling of 90 companies was carried out using the purposive sampling method. The hypothesis is tested with a one sample t-test or one sample Wilcoxon signed rank test. The results show that there was a negative market reaction to the change of name of companies listed on the Indonesia Stock Exchange in 2012-2022 on the first to the third day after the announcement of the company name change. This research provides additional empirical information regarding how the market reacts to a company name change.